STUDI KASUS TENTANG SISWA YANG MELANGGAR TATA TERTIB DI SMP NEGERI 7 PONTIANAK - Citra Ayu Ningtyas; Purwanti Purwanti; Abas Yusuf (Universitas Tanjungpura, 2018)
AbstractThis study aims to reveal about the relief efforts that will be given to students in SMP Negeri 7 Pontianak who often violate school rules. The method used is descriptive in the form of survey. The conclusion of this research is that it is known that the characteristic of case subject is in three consecutive three weeks of not entering school without permission, almost every day incomplete using school attribute, and colored hair, the subject of the case has been through the process of guidance, parent / guardian the subject of the case has been through a call. The cause factors are the follow-up of friends and the fear of a particular lesson. The counseling model used to assist case subjects is the REBT and Behavior counseling model. The result of the change is that the case subjects no longer violate school rules. The researcher's suggestion is that case subjects are expected to maintain and improve again the positive changes they have. Keywords : Case study, Students, Code of Conduct